Oil Recovery From Spent Bleaching Earth With Reflux Extraction Method Using Acetonitrile and n-Hexane Solvent - Maryudi Maryudi; Aster Rahayu; Totok Eka Suharto; Dhias Cahya Hakika; Ahmad Fatwa Zufar (Elkawnie, 2024)
Abstract: The growth of the oleochemical industry generated a large amount of spent bleaching earth (SBE) solid waste that causes environmental problems. The SBE solid waste produced is reported at about 600,000 metric tons per year. Recovery of the oil from SBE can be an alternative solution to reduce the negative impact of SBE solid waste. In this study, the recovery of oil from SBE was carried out by the reflux extraction method followed by a study on its properties. The oil recovery process was conducted by using two different solvents (acetonitrile and n-hexane) at different particle sizes (40, 60, 100 mesh) of SBE, solvent-SBE ratios (2:1, 3:1, 4:1), and extraction time (1, 2, 3 hours). Experimental results showed that n-hexane extracted oil with yield ranged from 5 to 14.8%, while acetonitrile extracted oil with yield ranged from 0.68 to 8.4%. Product analysis shows that the oil extracted has a water content of 1.56% and 2.53% for acetonitrile and n-hexane, respectively. The viscosity analysis results show that the oil viscosities were 5.83 cSt (acetonitrile) and 5.09 cSt (n-hexane) which is in reasonable agreement with the Indonesian National Standard for vegetable oil (SNI 7709:2019). The result suggested that n-hexane provided better product yield than acetonitrile as a solvent for oil recovery from SBE. This study provides an alternative method and solution for the oleochemical industry in managing SBE waste.Abstrak : Pertumbuhan industri oleokimia menghasilkan limbah padat berupa tanah pemucat (spent bleaching earth/ SBE) yang  mengakibatkan permasalahan lingkungan. Limbah padat SBE yang dihasilakn dilaporkan sekitar 600.000 ton per tahun. Pemisahan minyak dari SBE dapat menjadi alternatif penyelesaian masalah untuk menurunkan dampak negatif dari limbah SBE. Dalam penelitian ini, recovery minyak dari SBE dilakukan dengan metode ekstraksi reflux dan dilanjutkan karakterisasi hasil minyak. Recovery minyak dilakukan dengan dua jenis pelarut (asetonitril and n-heksana) dengan ukuran partikel SBE bervariasi (40, 60, 100 mesh), perbandingan pelarut-SBE (2:1, 3:1, 4:1), dan waktu ekstraksi (1, 2, 3 jam). Hasil penelitian menunjukkan bahwa asetonitril mengekstrak minyak dengan yield 1,56-2,53%, sementara n-heksana berkisar 5-14,8%. Minyak hasil ekstraksi menunjukkan kadar air 1.56% (asetonitril) and 2.53% (n-heksana), serta nilai viskositas sebesar 5.83 cSt (asetonitril) and 5.09 cSt (n-heksana). Minyak hasil memenuhi SNI Minyak goreng sawit (SNI 7709:2019). Hasil menunjukkan n-heksana memiliki kemampuan lebih baik dibanding asetonitril dalam mengekstrak minyak dari SBE. Hasil penelitian memberikan penyelesaian alternatif dalam menagngani limbah SBE dari industri oleokimia.